Occurrence of Colibacillosis in Broilers and Its Relationship With Avian Pathogenic Escherichia coli (APEC) Population Structure and Molecular Characteristics - Apostolakos, Ilias; Laconi, Andrea; Mughini-Gras, Lapo; Yapicier, Özlem Şahan; Piccirillo, Alessandra (Frontiers in Veterinary Science, 2021)
Avian pathogenic E. coli (APEC) causes colibacillosis, the disease with the highest economic loss for the broiler industry. However, studies focusing on the prevalence and population structure of APEC in the broiler production pyramid are scarce. Here, we used genotyping and serotyping data to elucidate the APEC population structure and its changes in different broiler production stages along with whole-genome sequencing (WGS) in a subset of APEC isolates to determine transmission patterns amongst dominant APEC sequence types (STs) and characterize them in detail. Comparison of genotypes encountered in both APEC and avian fecal E. coli (AFEC) provided further insights. Overall, APEC-related mortality, as the proportion of the total sampled mortality in the broiler production, was high (35%), while phylogroup C and serogroup O78 were predominant amongst APEC isolates. We found a low (34.0%) and high (53.3%) incidence of colibacillosis in chicks and end-cycle broilers, respectively, which may be related to a shift in APEC genotypes, suggesting a trend from commensalism to pathogenicity across different broiler production stages. Despite considerable APEC genotypic diversity, there was substantial genotype overlap (40.9%, overall) over the production stages and convergence of STs to the four clusters. Within these clusters, WGS data provided evidence of clonal transmission events and revealed an enriched virulence and resistance APEC repertoire. More specifically, sequenced APEC were assigned to defined pathotypes based on their virulence gene content while the majority (86%) was genotypically multi-drug resistant. Interestingly, WGS-based phylogeny showed that a subset of APEC, which are cephalosporin-resistant, may originate directly from cephalosporin-resistant AFEC. Finally, exploration of the APEC plasmidome indicated that the small fraction of the APEC virulome carried by IncF plasmids is pivotal for the manifestation of the APEC pathotype; thus, plasmid exchange can promote pathogenicity in strains that are at the edge of the commensal and pathogenic states.